Memory in Philosophy of Religion - Briedis, Mindaugas (My University, 2024)
This article analyzes the notion of memory in the philosophy of religion. The area of this problematic is defined by Descartes, who, in a thought experiment, postulates an all-powerful, evil demon capable of falsifying human perception. The problem of solipsism raised here also implies doubt about claims based on memory. Descartes’ assumptions are taken up constructively by Alvin Plantinga in his attempt to solve problems in the epistemology of religion by raising the following new question: is belief in God rational, and, if so, is it justified? Peter van Inwagen, for his part, uses memory analysis to construct arguments in support of theodicy. In considering these issues, other key topics within the philosophy of religion, such as the afterlife and the existence of the soul, which are closely related to the analysis of personal identity, inevitably arise.